1999
DOI: 10.1128/cmr.12.2.286
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Human Cytomegalovirus to Antiviral Drugs

Abstract: SUMMARY Resistance of cytomegalovirus (CMV) to antiviral agents is a well-recognized phenomenon that has been observed in the laboratory and in the clinical setting. Infections caused by antiviral-resistant CMV have been found exclusively among immunocompromised individuals, including patients with AIDS, bone marrow and solid-organ transplant recipients, and patients with hematologic malignancies, and in individuals with primary immunodeficiencies. The majority of these infections have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
145
1
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(158 citation statements)
references
References 67 publications
1
145
1
10
Order By: Relevance
“…However, in the setting of prolonged ganciclovir use, GCV-resistant CMV has been observed in solid-organ transplantation. 17 Bhorade et al 18 detected an incidence of GCV-resistant CMV disease of up to 6%, higher than previously reported in solid-organ transplantation. Although concerns over ganciclovir resistance have arisen in part due to the low bioavailability of oral drug formulations, 19 one report suggested that GCV prophylaxis does not select for resistant isolates of CMV.…”
Section: Discussionmentioning
confidence: 91%
“…However, in the setting of prolonged ganciclovir use, GCV-resistant CMV has been observed in solid-organ transplantation. 17 Bhorade et al 18 detected an incidence of GCV-resistant CMV disease of up to 6%, higher than previously reported in solid-organ transplantation. Although concerns over ganciclovir resistance have arisen in part due to the low bioavailability of oral drug formulations, 19 one report suggested that GCV prophylaxis does not select for resistant isolates of CMV.…”
Section: Discussionmentioning
confidence: 91%
“…This may reflect the decreased efficacy of ganciclovir in comparison to foscarnet due to the presence of the UL54 gene in these patients, which is associated with increased levels of ganciclovir resistance. 11,17 Another potential mechanism could be related to lack of prior immunologic memory to CMV in these patients, which appears necessary to efficiently clear CMV infection. 18,19 The development of higher levels of ganciclovir resistance due to UL54 mutations in this sub-group could also be attributed to longer periods of prophylaxis in mismatch patients.…”
Section: Discussionmentioning
confidence: 98%
“…11,12 Reported risk factors for development of ganciclovir resistance include being a seronegative recipient of a seropositive organ (D ϩ /R Ϫ ), prolonged exposure to oral ganciclovir and intense immunosuppression. 12,13,16 Despite multiple reports of ganciclovir-resistant CMV disease in solid-organ transplant recipients, optimal treatment regimens are unknown.…”
mentioning
confidence: 99%
“…Resistance to GCV is associated with mutations in one or both of the CMV DNA polymerase (UL54) and viral phosphotransferase (UL97). The majority of GCV resistance strains have mutations in the UL97 gene [10]. The UL97 mediates the initial phosphorylation of GCV which is needed for its antiviral action [11].…”
Section: Introductionmentioning
confidence: 99%
“…Deletions of the UL97 gene result in a drastic reduction in its efficiency by inhibiting CMV replication. Mutations in the viral DNA polymerase gene (UL54) can also increase GCV resistance and cross-resistance to other drugs [10].…”
Section: Introductionmentioning
confidence: 99%